2016
DOI: 10.1080/00450618.2016.1194474
|View full text |Cite
|
Sign up to set email alerts
|

High Performance Liquid Chromatography as a valuable tool for geoforensic soil analysis

Abstract: A key issue for geoforensic analysis is the ability to discriminate between geographical locations of close proximity, often with similar underlying geology. This paper addresses the lack of empirical research into the non-mineral components of sediment samples and presents the development of a method of sediment sample characterisation by High Performance Liquid Chromatography (HPLC) utilising the organic components of the sample. A sample preparation method and set of instrument parameters were developed suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 34 publications
1
11
0
Order By: Relevance
“…To the best of our knowledge, previous studies have not reported the retention time repeatability [24,27,28,[30][31][32]. Therefore, an accepted reference value of RSD in forensic soil analysis is unavailable in the literature.…”
Section: Rsd% = × S X 100%mentioning
confidence: 96%
See 4 more Smart Citations
“…To the best of our knowledge, previous studies have not reported the retention time repeatability [24,27,28,[30][31][32]. Therefore, an accepted reference value of RSD in forensic soil analysis is unavailable in the literature.…”
Section: Rsd% = × S X 100%mentioning
confidence: 96%
“…Three soil samples (red, brown and yellowishbrown soils) were collected from the fern garden of UKM, Malaysia. The soils were sampled following the gridpattern procedure described by Pye [6], which was successfully applied by McCulloch et al [30][31][32]. The procedure enables the researcher to assess the intralocation variability of the soil.…”
Section: Sample Preparationmentioning
confidence: 99%
See 3 more Smart Citations